Cell‐based high‐throughput screening identifies galactocerebrosidase enhancers as potential small‐molecule therapies for Krabbe's disease. Issue 11 (November 2016) - Jang, Dae Song; Ye, Wenjuan; Guimei, Tian; Solomon, Melani; Southall, Noel; Hu, Xin; Marugan, Juan; Ferrer, Marc; Maegawa, Gustavo H.B.
Abstract : Krabbe's disease, also known as globoid cell leukodystrophy (GLD), is a lysosomal storage disease caused by the deficiency of the lysosomal enzyme β‐galactocerebrosidase (GALC), resulting in severe neurological manifestations related to demyelination secondary to elevated galactosylsphingosine (psychosine) with its subsequent cytotoxicity. The only available treatment is hematopoietic stem cell transplantation, which delays disease onset but does not prevent long‐term neurological manifestations. This article describes the identification of small molecules that enhance mutant GALC activity, identified by quantitative cell‐based high‐throughput screening (qHTS). Using a specific neurologically relevant murine cell line (145M‐ Twi ) modified to express common human h GALC ‐G270D mutant, we were able to detect GALC activity in a 1, 536‐well microplate format. The qHTS of approximately 46, 000 compounds identified three small molecules that showed significant enhancements of residual mutant GALC activity in primary cell lines from GLD patients. These compounds were shown to increase the levels of GALC‐G270D mutant in the lysosomal compartment. In kinetic assessments, these small molecules failed to disturb the GALC kinetic profile under acidic conditions, which is highly desirable for folding‐assisting molecules operating in the endoplasmic reticulum and not affecting GALC catalytic properties in the lysosomal compartment. In addition, these small molecules rescued the decreased GALC activity at neutral pH and partially stabilized GALC under heat‐denaturating conditions. These drug‐like compounds can be used as the starting point to develop novel small‐molecule agents to treat the progressive neurodegenerative course of GLD. © 2016 Wiley Periodicals, Inc. Abstract : Through a quantitative cell‐based HTS against over 46, 000 compounds, three small molecules were identified and shown to enhance mutant galactocerobrosidase (GALC) in globoid‐cell leukodystrophy (GLD) patients cells. Further studies showed that the small molecules stabilize and increased mutant GALC levels in the lysosomes, being potential therapeutic agents for GLD.